Comparing Twitter and Facebook user behavior: Privacy and other aspects. (November 2015) - Buccafurri, Francesco; Lax, Gianluca; Nicolazzo, Serena; Nocera, Antonino
Highlights: We compare the behavior of users who belong to both Twitter and Facebook. We adopt a truly multi-OSN perspective by basing our analysis on membership overlap. We study overlapping friendship, user activity, degree, and privacy awareness. Abstract: Understanding online-social-network (OSN) user behavior is an important challenge in the field of social network analysis, as OSNs play a significant role in people's daily lives. So far, many studies considering only one OSN or, at most, comparing results obtained for a single OSN, have been provided. Nowadays, users typically join more OSNs and this is an important aspect that should be taken into account for user behavior analysis. In this paper, we give an important contribution in this direction, by analyzing the behavior of users belonging to bothFacebook andTwitter . This way, the analysis is well-founded because it is conducted on a common set of users and, further, a number of specific analyses become possible (as common friendship). Our study is carried out on data extracted from the web, and allows us to find important specificities of these users about their privacy setting, the choice of friends and the activity they do, which are generally consistent with the recent findings in this field.